A Content Analysis Revealing MPA Students' Unquestioning Followership as their Ethical Stance and the Implications for Ethical Competence. (2nd September 2020) - Perun, Stefan A.
Abstract : This articled reported the findings from a content analysis of two iterations of 131 Master of Public Administration (MPA) students' essays wherein they described their ethical stance for a standalone ethics course at a northeastern university. The analysis of the first iteration revealed that 35 of the students exhibited one or more of three follower archetypes; conformist, moralist, and/or relativist. A comparative analysis with the second iteration, revealed that 16 of these students never identified the deficiencies of their unquestioning followership perspective despite the interventions of the course. The findings suggested that prevailing definitions of ethical competence ought to explicitly include one's intentions to (a) evaluate all conduct in terms of consequences, (b) judge the virtuousness of the conduct based upon public service principles separate from organizational influence, (c) act virtuously, and (d) take full personal responsibility for all outcomes. The findings also suggested that inculcating ethical competence might be better achieved by creating cognitive dissonance with cases that demonstrate the deleterious effects of unquestioning followership. Areas for future research to understand how intent is shaped and evidenced in practice were identified.